2015
DOI: 10.1002/ange.201507696
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Properties of 2‐λ5‐Phosphaquinolines and 2‐λ5‐Phosphaquinolin‐2‐ones

Abstract: Treatment of 2‐ethynylanilines with P(OPh)3 gives either 2,2‐diphenoxy‐2‐λ5‐phosphaquinolines or 2‐phenoxy‐2‐λ5‐phosphaquinolin‐2‐ones under transition‐metal‐free conditions. This reaction offers access to an underexplored heterocycle, which opens up the study of the fundamental nature of the NPV double bond and its potential for delocalization within a cyclic π‐electron system. This heterocycle can serve as a carbostyril mimic, with application as a bioisostere for pharmaceuticals based on the 2‐quinolinone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 53 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Since 2015, we have been studying the properties of the rarely‐accessed phosphaquinolinone scaffold [10–14] . The heterocyclic core is structurally similar to both coumarin and carbostyril‐coumarin's aza‐counterpart‐the difference being that the carbonyl has been replaced with an isolobal phosphonyl group (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2015, we have been studying the properties of the rarely‐accessed phosphaquinolinone scaffold [10–14] . The heterocyclic core is structurally similar to both coumarin and carbostyril‐coumarin's aza‐counterpart‐the difference being that the carbonyl has been replaced with an isolobal phosphonyl group (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…X‐ray data of both forms suggested that the imidates possess more uniform bond lengths across the heterocyclic core, implying superior conjugation (Figure 2). [10] In prior studies, we have generally omitted data concerning the imidate form because of its facile hydrolysis into the amidate, and its inability to engender the hydrogen bond dimerization observed in the amidates. However, the inclusion of the 3‐pyridine motif in the core of the PN‐heterocycle dramatically increases imidate stability, affording a good opportunity to explore this species.…”
Section: Introductionmentioning
confidence: 99%
“…In this realm, the 2-(phenylethynyl)­aniline moiety has received much attention due to its aniline and o -alkyne functionalities in a single molecule. These molecules can be easily tuned in a way to synthesize a plethora of N -heterocyclic derivatives . Li and co-workers observed a remarkable transformation of 2-(phenylethynyl)­anilines with terminal alkynes leading to the formation of N -vinylindoles by using gold­(III) catalyst (Scheme a) .…”
mentioning
confidence: 99%